2020
DOI: 10.14393/rbcv72nespecial50anos-56467
|View full text |Cite
|
Sign up to set email alerts
|

Intersectando Geoestatística com Modelagem da Demanda por Transportes: um Levantamento Bibliográfico

Abstract: O planejamento de transportes depende da modelagem de variáveis que, em função de usualmente exigirem recursos elevados para a sua coleta, dispõem de uma amostragem limitada. Entretanto, uma vez que apresentam dependência espacial, a utilização da Geoestatística na modelagem da demanda por transportes se mostrou bastante conveniente, já que esse ferramental permite a obtenção de estimativas em locais não amostrados. Nesse contexto, a linha de pesquisa voltada a aplicações da Geoestatística na previsão da deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[24] stated that geostatistics is one of the procedures for analyzing space-time data that takes into account the existing interactions between spatial and temporal components, allowing interpolations in time and space. Among the advantages of using geostatistics, according to [25], is the fact that it is a tool that can use as much information as is available with respect to the variable of interest-which is difficult to collect-to estimate its values in non-sampled locations through the generation of a continuous surface of estimated points.…”
Section: Introductionmentioning
confidence: 99%
“…[24] stated that geostatistics is one of the procedures for analyzing space-time data that takes into account the existing interactions between spatial and temporal components, allowing interpolations in time and space. Among the advantages of using geostatistics, according to [25], is the fact that it is a tool that can use as much information as is available with respect to the variable of interest-which is difficult to collect-to estimate its values in non-sampled locations through the generation of a continuous surface of estimated points.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of data on travel demand variables, which are usually spatially discrete, has led to an increasing number of geostatistical applications to travel demand modeling, with results that represent an important contribution to the planning and operation of transport systems (Gomes et al, 2018;Lindner and Pitombo, 2019;Marques and Pitombo, 2021a;Yang et al, 2018;Zhang and Wang, 2014). Several studies using Geostatistics for spatially estimate travel demand variables can be found in the bibliographic review by Marques and Pitombo (2020). Along these studies, the spatial dependence of travel demand variables is confirmed by the wellstructured variograms calculated in the geostatistical modeling step.…”
Section: Introductionmentioning
confidence: 99%